Diseño de una herramienta basada en estrategias de gamificación para el aprendizaje de niños con Trastorno de Déficit de Atención (TDA) entre 6 y 10 años (2020)
In the country there is a high number of children with attention deficit trauma (ADD), this due to the low inclusion and the lack of tools to treat the child. This industrial design project seeks to increase the attention and motivation of children between 6 and 10 years old by carrying out learning activities under educational competences (mathematics, language and science) in real contexts and moments where the child can experiment and detail each element. , behavior and action given in space in a much more effective way and using gamification generates a much more innovative and attractive experience that could increase the child's learning by 80%. The design of a tool that manages to link educational and gamification concepts, with characteristics of use, form and function, was intended to create activities that involve the child in a new form of learning that changes the traditional dynamics that currently exist, for one that Take advantage of the special qualities of TDA along with the characteristics of the context. For the development of this tool, an ergonomic variability study was carried out that considered the aspects (human, objective and spatial) that involve the activity of learning and thus prioritize and study them to obtain an analysis of requirements and precise and detailed determinates. Its shape started from the deconstruction of basic polygons, passing through iterative transformations of sketching, modeling and 3D rendering that denote the materials and their colors. From here the scope is a conceptual beta prototype, due to the conditions of time and health (COVID-19). Finally, a design tool was obtained with a family of objects and a gamification strategy that manages to link all the main aspects mentioned above.